LIGHT-HUMUS CARBONATE-ACCUMULATIVE AND PALE-METAMORPHIC SOILS IN THE COLLECTION OF V. V. DOKUCHAEV CENTRAL SOIL MUSEUM: VERIFICATION OF DIAGNOSTICS AT TYPE LEVEL - E. A. Gurkova; M. A. Bronnikova; M. I. Gerasimova; E. Y. Sukhacheva; Y. V. Konoplyanikova (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
Results of 24 soil monoliths studying in the collection of Dokuchaev Central Soil Museum were analyzed in terms of diagnostic criteria in Russian soil classification system; these were chestnut, brown aridic, pale and cryoaridic soils. The topsoils of chestnut and brown aridic soils meet the criteria for the light-humus horizon (AJ), but their values in Munsell readings proved to be lower. In pale soils, the upper horizons were identified as gray-humus instead of light-humus ones as prescribed in the system. The cryohumus AK horizon, diagnostic for cryoaridic soils, is peculiar by the abundance of reddish frost-fragmented plant residues (detritus). We failed to differentiate metamorphic BM and xerometamorphic BMK horizon, they had more features of the latter. Both horizons are similar to the pale-metamorphic BPL horizon in color, although the BPL has a definitely weaker structure displaying some cryogenic features. These are less prominent in cryoaridic soils than in pale soils, hence, the diagnostic BPL horizon in cryoaridic soils may be removed to the category of diagnostic property. A similar re-evaluation may be proposed for the carbonate-textural CAT horizon: to consider it as a diagnostic property in the carbonate-accumulative horizon (ВСАt). The ВСА horizon in all soils studied differed by carbonate pedofeatures, namely, segregations in brown and chestnut soils, impregnations in pale soils, impregnations and coatings in cryoaridic soils.